Respon Pondok Pesantren Terhadap Pembaruan Pendidikan Islam di Indonesia - M Khumaidi (FALASIFA : Jurnal Studi Keislaman, 2017)
ABSTRACTIn the history of Pesantren is growing and the number reaches thousands.According to the report book released by the Ministry of Religious Affairs in1982, the number of pesantren in Indonesia was recorded at 4,890 pieces. In thespan of 22 years later (between 1982 and 2004), the number of Pesantren hasincreased in line with the establishment of pesantren in various corners of thecountry, especially during the current order of reform. The contradictoryIndegenousity of pesantren differs from the practice of education in othereducational institutions, this is what causes the dynamics as well as the problemsthat arise in Pesantren as well - at least - featuring a characteristic and exoticcharacter.Keyword: Pondok Pesantren, Renewal of Islamic Education in Indonesia